A philosophy of struggle : the Leonard Harris reader : philosophia nata ex conatu - Harris, Leonard, 1948-; McBride, Lee A., III (London, England : Zed Books, 2020)
"Collating, for the first time, the key writings of Leonard Harris, this volume introduces readers to a leading figure in African-American and liberatory thought. Harris' writings on honor, insurrectionist ethics, tradition, and his work on Alain Locke have established him as a leading figure in critical philosophy. His timely and urgent responses to structural racism and structural violence mark him out as a bold cultural commentator and a deft theoretician. The wealth and depth of Harris' writings are brought to the fore in this collection and the incisive introduction by Lee McBride serves to orient, contextualize, and frame an oeuvre that spans four decades. In his prolegomenon, Harris eschews the classical meaning of ?philosophy,? supplanting it with an idiosyncratic conception of philosophy- philosophia nata ex conatu -that features an avowedly value-laden dimension. As well as serving as an introduction to Harris' philosophy, A Philosophy of Struggle provides new insights into how we ought conceptualize philosophy, race, tradition, and insurrection in the 21st century."--
Part I: Prolegomenon. What, then, is "Philosophy Born of Struggle"? : Philosophia nata ex conatu : (philosophy as, and sourced by, strife, tenaciousness, organisms striving} -- Part II: Immiseration and racism (oppressions as nacro-being). The concept of racism : an essentially contested concept? (1998) -- What, then, is racism? (1999) -- Nacro-being : an actuarial account of racism (2018) -- Part III: Honor and dignity (reason and efficacious agency). Autonomy under duress (1992) -- Honor : emasculation and empowerment (1992) -- Tolerance, reconciliation, and groups (2003) --
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Harris, Leonard, -- 1948-; African American philosophy; Race relations -- Philosophy; African Americans; Social & political philosophy; Electronic books